Pathomorphological Patterns of Placental Dysfunction in Late Manifestation of Fetal Growth Restriction - Zhurakivska, Oksana; Yarotska, Yuliia; Govsieiev, Dmytrо; Ostrovska, Oksana; Rymarchuk, Mariana (Acta medica Lituanica, 2025)
Fetal growth restriction is one of the main factors contributing to neonatal mortality, stillbirth, and cardiovascular dysfunction in a fetus and newborn, where one of the common causes is placental dysfunction; it can occur as a result of placental vascular anomalies, which requires clarification and systematization of existing scientific provisions based on the assessment of morphological patterns of fetoplacental circulatory disorders.The aim of the study was to investigate and evaluate morphological markers of fetoplacental blood flow disorders in late manifestation of fetal growth restriction by pathohistological examination of placental tissue.Materials and methods: Clinical and anamnestic features were assessed in 80 pregnant women with late manifestation of fetal growth restriction (the main group of research) and in 40 patients with a timely labour and birth of fetuses with normal fetometry parameters for the gestational age. 32 and 10 placental tissue samples were selected in the main group and in the comparison group, respectively, for pathohistological examination, and a postnatal macro-histomorphological assessment of the placenta was performed.Results: Postnatal macromorphometric characteristics of placental tissue reflect pathological features of its formation, dominated by an abnormal shape (46–57.5%), eccentric umbilical cord insertion (43–53.8%) with main and intermediate types of vascular branching (37–46.2%), and a statistically lower placental weight and diameter. A combination of maternal and fetal vascular malperfusion was noted, with the following most significant markers: infarctions (13–40.6%), distal villous hypoplasia (24–75.0%), increased syncytial nodules as a manifestation of delayed villous maturation as a manifestation of premature maturation (24–75.0%), decidual arteriopathy (13–40.6%). Analysis of histopathological data indicates malperfusion of the fetal vessels, with the proportion of villitis and markers of intrauterine infection verified in one third of the samples (13–40.6%).Conclusions: In cases of late-onset fetal growth restriction, placental lesions occur with the development of maternal and fetal vascular malperfusion. Pathomorphological criteria of maternal vascular malperfusion are statistically significant in the main group: infarctions, distal villous hypoplasia, decidual arteriopathy, and chorionic villous dysmaturation. Fetal vascular malperfusion is characterized by obliteration and thrombosis of the stem vessels of the anchoring and intermediate villi, avascularization, hyalinosis of the villi, and, less frequently, delayed maturation with the development of stromal-vascular karyorexis. In our study, both Type 1 and Type 2 fetal vascular malperfusion in different placentas with fetal growth restriction were found, but the segmental type was still the most common.
Keywords: fetal growth restriction; placenta; maternal vascular malperfusion; fetal vascular malperfusion; postnatal macro-histomorphological examination